2009
DOI: 10.1007/s11103-009-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of genes encoding FK506-binding proteins in rice

Abstract: The FK506-binding proteins (FKBPs) are a class of peptidyl-prolyl cis/trans isomerase enzymes, some of which can also operate as molecular chaperones. FKBPs comprise a large ubiquitous family, found in virtually every part of the cell and involved in diverse processes from protein folding to stress response. Higher plant genomes typically encode about 20 FKBPs, half of these found in the chloroplast thylakoid lumen. Several FKBPs in plants are regulators of hormone signalling pathways, with important roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 117 publications
(180 reference statements)
0
52
1
1
Order By: Relevance
“…The unusual FK506-binding domain in TWD1 was instead found to participate in protein interaction with ABCB-type auxin transporters and is apparently involved in the functional regulation of these transporters [44] (see Section 4). TWD1 also possesses a tetratricopeptide repeat domain (common [131] Regulation and PM-to-ER trafficking of ABCB-type auxin transporters [8,9] Z. mais [133] Interaction with ABCB transporters on PM (via FKB-domain) [8,62], ABCC transporters on tonoplast (via TPR domain) [66], with HSP90 (TPR domain) [62,65] and calmodulin (calmodulin-binding domain) [66] Over-expression of TWD1 lacking its membrane anchor results in hypermorphic growth [64] FKBP72/PAS1 A. thaliana [69] Unclear (C-terminal membrane anchor), nuclear [68,134] Low, inhibited by FK506 and rapamycin [134] Up-regulated cell division, leaf fusions, short hypocotyls, sterile [69] O. sativa [131] Chaperon during translocation of NAC-like transcription factor (AtFAN) into nucleus [68] Z. mais [133] Regulation of very long fatty acid elongation [70] -DGT/CypA/ROC1/CYP1/CYP2/ P. patens [10] Nuclear and cytoplasmic [10,90], phloem sieve elements [79] Significant [77,78], inhibited by CsA [78] Regulates growth [90], gene expression [84,90,92], patterned cell division [88], phloem function [79], ROS balance in root apical meristem [87] A. [137] in many large immunophilins) that was shown to interact with vacuolar ABC transporters of the C subclass and HSP90 [65,66], as w...…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
“…The unusual FK506-binding domain in TWD1 was instead found to participate in protein interaction with ABCB-type auxin transporters and is apparently involved in the functional regulation of these transporters [44] (see Section 4). TWD1 also possesses a tetratricopeptide repeat domain (common [131] Regulation and PM-to-ER trafficking of ABCB-type auxin transporters [8,9] Z. mais [133] Interaction with ABCB transporters on PM (via FKB-domain) [8,62], ABCC transporters on tonoplast (via TPR domain) [66], with HSP90 (TPR domain) [62,65] and calmodulin (calmodulin-binding domain) [66] Over-expression of TWD1 lacking its membrane anchor results in hypermorphic growth [64] FKBP72/PAS1 A. thaliana [69] Unclear (C-terminal membrane anchor), nuclear [68,134] Low, inhibited by FK506 and rapamycin [134] Up-regulated cell division, leaf fusions, short hypocotyls, sterile [69] O. sativa [131] Chaperon during translocation of NAC-like transcription factor (AtFAN) into nucleus [68] Z. mais [133] Regulation of very long fatty acid elongation [70] -DGT/CypA/ROC1/CYP1/CYP2/ P. patens [10] Nuclear and cytoplasmic [10,90], phloem sieve elements [79] Significant [77,78], inhibited by CsA [78] Regulates growth [90], gene expression [84,90,92], patterned cell division [88], phloem function [79], ROS balance in root apical meristem [87] A. [137] in many large immunophilins) that was shown to interact with vacuolar ABC transporters of the C subclass and HSP90 [65,66], as w...…”
Section: Plant Immunophilins Are Implicated In Regulation Of Developmentmentioning
confidence: 99%
“…Introduction of this change into Fkbp12 reduces PPIase activity by approximately eightfold and rapamycin and FK506 binding affinity by 10-and 75-fold, respectively. It is therefore likely that Shutdown does not represent an optimally active PPIase and may instead utilize the domain as a protein interaction interface, as do other FKBP family members (Gollan and Bhave 2010).…”
Section: à46mentioning
confidence: 99%
“…The FKBP domain is annotated as a peptidyl-prolyl cistrans isomerase (PPIase), though there are many instances of well-conserved FKBP domains that lack PPIase activity (Gollan and Bhave 2010). The macrolide immunosuppressants FK506 (tacrolimus) and rapamycin (sirolimus) bind with sub-nanomolar affinity to the FKBP domain and block a key protein-protein interaction surface, but as is the case with PPIase activity, many family members display much reduced affinities for these compounds (DeCenzo et al 1996;Gollan and Bhave 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We obtained the 29 FKBP sequences of rice according to Gollan and Bhave (2010). Along with the 30 FKBPs in maize, there were 59 FKBPs in all for construction of the phylogenetic tree.…”
Section: Phylogenetic Tree Constructionmentioning
confidence: 99%
“…In recent years, studies have carried out several valuable functional characterizations of individual plant FKBPs, but the identification and analyses of all FKBPs have only been in Arabidopsis (He et al, 2004;Romano et al, 2005) and Oryza sativa (rice) (Gollan and Bhave, 2010) genomes, which have revealed the true size and character of the FKBP family in higher plants. Bioinformatics have opened up new and highly efficient analysis and research approaches (Staskawicz et al, 1995), and can be used to conduct a comprehensive and complete analysis of the basic data of the whole genome with regard to FKBP genes, which play an important role in large-scale gene isolation, gene functional annotation and functional genomics studies.…”
Section: Introductionmentioning
confidence: 99%